NILAI AMBANG PROKALSITONIN DAN RISIKO KEMATIAN DINI PADA ABSES LEHER DALAM: PERSPEKTIF KLINIS: procalciton pada abses leher dalam - Asyari, Ade; Tri Novriansyah, Wahyu; Novialdi, Novialdi; Dia Rofinda, Zelly; Rasyid, Rosfita; Utami, Refi Amalia (PERHATI-KL, 2025)
Background: Procalcitonin (PCT) is widely used as an inflammatory marker in sepsis, but still controversial in deep neck abscesses. Purpose: To evaluate the usefulness of PCT as outcome predictor in deep neck abscess. Method: A prospective observational cohort study was conducted at Dr. M. Djamil Hospital, Padang, Indonesia (March 2022–May 2023). Patients with confirmed deep neck abscess by pus aspiration in the Emergency Department were included. Baseline laboratory and serum PCT tests were performed before surgical drainage. All patients received broad-spectrum antibiotics and standard postoperative care. Assessed outcomes were mortality, septic shock, organ failure, mediastinitis, empyema/ pleural effusion, necrotizing fasciitis, tracheostomy, pharyngocutaneous fistula, Intensive Care Unit >24 hours, and hospital stay. Result: Thirty-five patients met inclusion criteria. Multiple neck space involvement was found in 74.3%, and 93.4% underwent surgery. Mortality occurred in 28.6%, septic shock in 20%, mediastinitis in 14.3%, empyema/pleural effusion in 11.4%, necrotizing fasciitis in 8.6%, tracheostomy in 5.7%, fistula in 8.6%, and ICU stay >24 hours in 20%. Mean hospital stay was 9.03±7.90 days. Mean admission PCT was 0.313±0.677 ng/mL, with 17.1% having elevated PCT>0.5 ng/mL. No significant correlation was found between PCT and overall outcome. However, Receiver Operating Characteristic (ROC) analysis showed PCT≥0.14 ng/mL, predicted <5-day mortality (sensitivity 85.7%, specificity 78.4%), Area Under Curve (AUC) 0.773, p=0.027). Conclusion: Procalcitonin showed potential as an adjunctive marker in deep neck abscess. Although low initial levels are frequent, they do not exclude severe complications, highlighting its role in early risk stratification and clinical decisions.